2023
DOI: 10.1039/d2qm01193j
|View full text |Cite
|
Sign up to set email alerts
|

An electrical microenvironment constructed based on electromagnetic induction stimulates neural differentiation

Abstract: A NH2-MXene/PLLA nerve conduit with a conductive network structure is constructed by laser additive manufacturing, which can generate electrical signals driven by electromagnetic induction, and the generated electrical signals can promote the differentiation of nerve cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Compared with other groups, the PLLA/Bi 2 S 3 –BaTiO 3 bone scaffold exhibited a higher cell count and improved cell spreading when exposed to light and ultrasound stimulation. It was observed that adjacent cells overlapped, suggesting that the enhanced electrical stimulation of the bone scaffold may be responsible for these effects. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other groups, the PLLA/Bi 2 S 3 –BaTiO 3 bone scaffold exhibited a higher cell count and improved cell spreading when exposed to light and ultrasound stimulation. It was observed that adjacent cells overlapped, suggesting that the enhanced electrical stimulation of the bone scaffold may be responsible for these effects. , …”
Section: Resultsmentioning
confidence: 99%
“…It was observed that adjacent cells overlapped, suggesting that the enhanced electrical stimulation of the bone scaffold may be responsible for these effects. 36,37 After 3 days of cell culture, the viability of cells on different bone scaffolds was assessed using a live/dead fluorescence staining assay. 38 In this assay, live cells were stained green, while dead cells were stained red.…”
Section: Biological Properties Of Bone Scaffoldsmentioning
confidence: 99%
“…After ultrasonically stirring and drying, the mixed powder was further mechanically ground for 30 min. A PPDO/Cu@ZIF-8 porous skin scaffold was prepared by a selective laser sintering (SLS) technique according to the previous process. The preparation parameters were set as a laser scanning speed of 400 mm/s, laser power of 6 W, a line spacing of 0.24 mm, and a monolayer thickness of 0.15 mm. In addition, the PPDO/ZIF-8 and PPDO scaffolds were prepared with the same parameters set as the comparison groups.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the hydrophilicity of all scaffolds was evaluated because it could influence cell adhesion and proliferation. [57][58][59] Obviously, the PLLA scaffold exhibited hydrophobicity ascribed to its water contact angle reaching 90°(Fig. 6a).…”
Section: Cell Activitymentioning
confidence: 99%